Enhanced selectivity in the conversion of glycerol to pyridine bases over HZSM-5/11 intergrowth zeolite. Issue 38 (2nd May 2017) - Zhang, Yuecheng; Zhai, Xing; Zhang, Hongyu; Zhao, Jiquan
Abstract : Intergrown zeolite HZSM-5/11(78) catalyst showed enhancement in the conversion of glycerol with ammonia to pyridine bases. Abstract : A composite co-crystalline zeolite HZSM-5/11(78) was synthesized and tested in the conversion of glycerol with ammonia to pyridine bases (pyridine, 2-methylpyridine, 3-methylpyridine). The HZSM-5/11(78) showed good performance compared to other zeolites with similar Si/Al ratios such as HZSM-5(80), HZSM-11(80) and the physical mixture of HZSM-5(80) and HZSM-11(80). Characterization results from the N2 adsorption–desorption and IR of the adsorbed pyridine indicated that the good performance of HZSM-5/11(78) was related to the higher surface area and co-existence of an appropriate ratio of Lewis and Brønsted sites, which are derived from the intergrowth between zeolites HZSM-5 and HZSM-11. The parameters affecting the catalytic performance of HZSM-5/11(78) were investigated systematically. The optimal conditions for producing pyridine bases from glycerol with ammonia over this catalyst were determined, including a reaction temperature of 520 °C, 0.1 MPa pressure with a molar ratio of ammonia to glycerol of 12 : 1, and a GHSV of 300 h −1 .